Bi-specific autoantigen-T cell engagers as targeted immunotherapy for autoreactive B cell depletion in autoimmune diseases - Perico, Luca; Casiraghi, Federica; Sônego, Fabiane; Todeschini, Marta; Corna, Daniela; Cerullo, Domenico; Pezzotta, Anna; Isnard-Petit, Patricia; Faravelli, Silvia; Forneris, Federico; Thiam, Kader; Benigni, Ariela; et al. (Frontiers in Immunology, 2024)
In autoimmune diseases, autoreactive B cells comprise only the 0.1-0.5% of total circulating B cells. However, current first-line treatments rely on non-specific and general suppression of the immune system, exposing patients to severe side effects. For this reason, identification of targeted therapies for autoimmune diseases is an unmet clinical need. Here, we designed a novel class of immunotherapeutic molecules, Bi-specific AutoAntigen-T cell Engagers (BiAATEs), as a potential approach for targeting the small subset of autoreactive B cells. To test this approach, we focused on a prototype autoimmune disease of the kidney, membranous nephropathy (MN), in which phospholipase A2 receptor (PLA2R) serves as primary nephritogenic antigen. Specifically, we developed a BiAATE consisting of the immunodominant Cysteine-Rich (CysR) domain of PLA2R and the single-chain variable fragment (scFv) of an antibody against the T cell antigen CD3, linked by a small flexible linker. As such, the BiAATE creates an immunological synapse between autoreactive B cells bearing an CysR-specific surface Ig + and T cells. Ex vivo, the BiAATE successfully induced T cell-dependent depletion of PLA2R-specific B cells isolated form MN patients, sparing normal B cells. Systemic administration of BiAATE to mice transgenic for human CD3 reduced anti-PLA2R antibody levels following active immunization with PLA2R. Should this approach be confirmed for other autoimmune diseases, BiAATEs could represent a promising offthe-shelf therapy for precision medicine in virtually all antibody-mediated autoimmune diseases for which the pathogenic autoantigen is known, leading to a paradigm shift in the treatment of these diseases.